The Fukushima Daiichi NPP Accident, Its After Effects And The Lessons Learnt From It - Aziz, Md Akhlak Bin; Huq, Md Fazlul; Mahmood, Zahid Hasan; Kabir, Khorshed Ahmad (Journal of Bangladesh Academy of Sciences, 2018)
A tsunami induced by an earthquake of magnitude nine hit the Fukushima Daiichi NPP on 11th March, 2011. A seawall of only 10 m high above sea level against tsunami waves of 15 m, led to a series of catastrophic events like inundation of the backup diesel generators exceptionally located at the basement, hydrogen explosions at three units etc. Immediate evacuation and efficient management ensured negligible harmful effects due to radiation exposure. By 2012, 160,000 people were evacuated. Government gave land and housing to evacuees and an additional USD 1030 per month for psychological suffering. But evacuees were not allowed to return to regions with radiation of 20-50 mSv/y despite IAEA effective dose limit for one year being 50 mSv. Moreover, dose limit for clean up workers were also set at 250 mSv compared to international allowable limit of 500 mSv. Post accidents efforts taken by the government were praiseworthy but a less conservative limit to allow return of evacuees could have saved a lot more people. Journal of Bangladesh Academy of Sciences, Vol. 42, No. 1, 55-66, 2018